2001
DOI: 10.1159/000047173
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Protein A and B Genetic Variants and Respiratory Distress Syndrome: Allele Interactions

Abstract: The contribution of multiple genetic components in disease pathogenesis is relevant to both diseases of multifactorial and/or multigenic etiology such as the respiratory distress syndrome (RDS) and to diseases where a single gene has been identified as the disease-causing gene. An example of the latter is cystic fibrosis (CF) where the disease-causing gene has been clearly identified as the CF transmembrane conductance regulator gene, but genetic variants of the mannose binding protein and surfactant protein A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
1
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 29 publications
1
15
1
1
Order By: Relevance
“…The results of population-based studies (Kala et al, 1998;Haataja et al, 2000Haataja et al, , 2001Ramet et al, 2000;Floros and Fan, 2001;Floros et al, 2001a, b;Marttila et al, 2003a, b) show significant associations between certain subgroups of IRDS and certain SP-A alleles. Some inconsistencies between studies are found possibly arising due to racial differences or differences in diagnostic criteria and perhaps confounders like degree of prematurity, steroid therapy, or multiple birth .…”
Section: Infant Respiratory-distress Syndrome (Irds)mentioning
confidence: 99%
“…The results of population-based studies (Kala et al, 1998;Haataja et al, 2000Haataja et al, , 2001Ramet et al, 2000;Floros and Fan, 2001;Floros et al, 2001a, b;Marttila et al, 2003a, b) show significant associations between certain subgroups of IRDS and certain SP-A alleles. Some inconsistencies between studies are found possibly arising due to racial differences or differences in diagnostic criteria and perhaps confounders like degree of prematurity, steroid therapy, or multiple birth .…”
Section: Infant Respiratory-distress Syndrome (Irds)mentioning
confidence: 99%
“…These associations may be also dependent on SP-B polymorphisms (188, 192, 193), and influenced by multiple birth and birth order (187, 190), antenatal glucocorticoid therapy (11, 194, 195), size of the uterus and length of gestation (2). The SP-A1 6A 2 /6A 2 genotype association with RDS susceptibility was also found to be influenced by multiple birth, being associated with risk when twins were concordant for RDS, or protective when twins were discordant for RDS (187, 190).…”
Section: Association Of Sp-a and Sp-d Polymorphisms With Diseasementioning
confidence: 99%
“…SP-B and SP-C play a key role in the surface tension lowering activity of surfactant, and SP-A and SP-D are important for the host defense function of the lung. Genetic variants of these genes have been associated with inflammatory lung diseases, such as respiratory distress syndrome (RDS), acute RDS (ARDS), chronic obstructive pulmonary disease (COPD), and lung cancer (19)(20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%